DEVELOPING A MATURITY MODEL FOR INDUSTRY 4.0 : Test runs in the Finnish machine manufacturing industry - Rantanen, Leevi (My University, 2019)
Industry 4.0 is a popular topic in both academic and non-academic literature. It is often defined as the fourth industrial revolution or the digitalization of the manufacturing industry. Findings from the literature imply that it is beneficial for organizations to assess their capabilities regarding industry 4.0. A maturity model is a proper solution for this, organizations can see their situation and where they could improve, as well as do benchmarking with other organizations based on the maturity results. The objective of this research was to develop a maturity model for assessing Industry 4.0 capabilities and to pilot-test the model to see what kind of results it provides from the Finnish machine manufacturing industry. Several Industry 4.0 maturity models already exist, but there is continuously more and more research available regarding Industry 4.0 and its related concepts develop over time. Therefore, it is necessary that a new maturity model is developed to ensure that there is a relevant instrument for assessing Industry 4.0 capabilities now and in the future. This research was carried out using a constructive research approach. An initial Industry 4.0 maturity model was developed based on Industry 4.0 literature, existing Industry 4.0 maturity models as well as literature about designing a maturity model. This model was then evaluated by five Finnish machine manufacturing companies in interviews and was developed further based on empirical findings. The final model was pilot-tested in the same companies to see how advanced they are regarding Industry 4.0 capabilities. The final model measures Industry 4.0 capabilities in six different dimensions. Most of the content of the initial model stayed the same after being validated in the interviews, but two dimensions were added based on them. The average level of maturity in the pilot-test was quite intermediate. The level of maturity was the highest in the technological dimension of Industry 4.0. More research regarding the whole Industry 4.0 transformation is required and new models must be developed over time. These models should also be widely applied to get extensive and generalizable results.

Industry 4.0 on yleinen aihe niin akateemisessa, kuin muussakin kirjallisuudessa. Se määritellään usein neljänneksi teolliseksi vallankumoukseksi, tai valmistavan teollisuuden digitalisoitumiseksi. Tulokset kirjallisuudesta osoittavat, että Industry 4.0 -kyvykkyyksien arviointi on organisaatioille tärkeää. Maturiteettimallin avulla organisaatiot voivat nähdä oman tilanteensa sekä missä ja miten he voisivat parantaa. Lisäksi maturiteetin tuloksia voidaan vertailla muiden organisaatioiden kanssa benchmarking-näkökulmasta. Tämän tutkimuksen tavoitteena oli luoda maturiteettimalli, jolla arvioidaan Industry 4.0 -kyvykkyyksiä. Valmista mallia testattiin viidessä suomalaisessa laitteita valmistavassa organisaatiossa, jotta selviäisi millaisia tuloksia sillä saadaan. Useita Industry 4.0-maturiteettimalleja on jo olemassa, mutta tutkimuksen lisääntyessä ja Industry 4.0-konseptien kehittyessä on tärkeää, että uusi maturiteettimalli kehitetään varmistamaan, että relevantti mittausinstrumentti Industry 4.0 -kyvykkyyksille on olemassa. Tämä tutkimus on tehty soveltaen konstruktiivista tutkimusotetta. Alustava maturiteettimalli luotiin Industry 4.0 -kirjallisuuden, olemassa olevien Industry 4.0-maturiteettimallien sekä maturiteettimallien luomiseen liittyvän kirjallisuuden pohjalta. Viisi suomalaista laitevalmistajaa arvioi tätä mallia haastatteluissa ja empiiristen tulosten perusteella mallia kehitettiin lisää. Valmista mallia testattiin samoissa organisaatioissa, jotta saataisiin selville, miten edistyneitä ne ovat Industry 4.0 -kyvykkyyksiltään. Valmis malli mittaa Industry 4.0 -kyvykkyyksiä kuudessa eri dimensiossa. Suurin osa alkuperäisen mallin sisällöstä pysyi samana, mutta kaksi dimensiota lisättiin malliin haastatteluiden pohjalta. Testitulokset suomalaisen laitteita valmistavien organisaatioiden maturiteetista olivat kokonaisuudessaan keskitasoa, mutta edistyksellisimpiä organisaatiot olivat Industry 4.0:n teknologisissa ulottuvuuksissa. Lisää kirjallisuutta Industry 4.0-transformaatiosta tarvitaan ja uusia maturiteettimalleja täytyy kehittää ajan kuluessa. Näitä uusia malleja täytyy myös soveltaa laajasti, jotta saadaan laajamittaisia ja yleistettäviä tuloksia.
Keywords: Industry 4.0, maturity model, manufacturing industry, machine manufacturing